The doodle revolution unlock the power to think differently - Brown, Sunni (Portfolio Penguin, 2014)
"A fearless guide to awakening your mind using simple visual language What do Einstein, Edison, Richard Feynman, Henry Ford, and JFK have in common? Like virtually all heavy-hitting thinkers, they looked beyond just words and numbers to get intellectual and creative insights. They actively applied a deceptively simple tool to think both smarter and faster: the doodle. And so can the rest of us-zero artistic talent required. Visual thinking expert Sunni Brown has created The Doodle Revolution as a kick-starter guide for igniting and applying simple visual language to any challenge. The instinctive and universal act of doodling need only be unleashed in order to innovate, solve problems, and elevate cognitive performance instantly. With humor, wit, and a commitment to disrupting our perceptions of doodling, Brown teaches us how to: Doodle any object, concept, or system imaginable. Invent, innovate, and solve messy problems. Transform text into a visual display that engages an audience. Explain the relevance of visual literacy to leaders at work and at school. Despite what our culture suggests, doodling and sketching are powerful tools and they are for everyone, not just artsy types. It's time we recognize visual literacy as a fundamental requirement for the future"-- Provided by publisher.